Adoption of Artificial Intelligence and Digital Resources among Academicians of Islamic Higher Education Institutions in Indonesia - Suwendi, Suwendi; Mesraini; Bakti Gama, Cipta; Rahman, Hadi; Luhuringbudi, Teguh; Masrom, Maslin (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2025)
This study aimed to assess the readiness, attitudes, knowledge, and skills of lecturers in using artificial intelligence (AI) and electronic resources (ER) to enhance academic capacity. Understanding this adoption level is crucial for effectively integrating AI and ER into educational practices. In addition, this study contributes both theoretically and practically to digital scholarship by enhancing digital adoption and competence in education. This mixed-method study captured individual experiences and statistical trends related to digital scholarship in higher education. The qualitative method includes interviews, while the quantitative method involves survey questionnaires. The study focuses on lecturers from Islamic higher education institutions (IHEIs) in Indonesia. The results indicate that while lecturers rarely use AI and ES, they recognize the potential of digital technology in academic tasks. Despite limited exposure to AI and ER, IHEI lecturers in Indonesia can define these technologies accurately. Most lecturers actively update their knowledge and consider bias and ethical aspects in AI and ES usage. Regarding skills, over 60% of respondents reported proficiency in using AI and ES, suggesting a growing level of digital competence. These findings suggest that while many IHEI lecturers in Indonesia are prepared to adopt AI and ER, further support may be needed to ensure widespread acceptance.